A plugging agent for carbon dioxide gas drive well and preparation method thereof

By using oil well cement, nano calcium carbonate, modified silica, water reducing agent, modified montmorillonite and porous magnesium oxide particles in the carbon dioxide gas-driving leak plugging agent, the problems of low strength and poor sealing after curing of the leak plugging agent are solved, and efficient leak plugging effect is achieved.

CN119059764BActive Publication Date: 2025-03-14KARAMAY HONGDU
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411555529.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-03-14
Estimated Expiration
2044-11-04

AI Technical Summary

Technical Problem

The existing carbon dioxide gas well leak plugging agent is not strong after curing, resulting in incomplete leak plugging and still has the problem of leakage.

Method used

A leak plugging agent including oil well cement, nano calcium carbonate, modified silica, water reducing agent, modified montmorillonite and porous magnesium oxide particles is used. Through the combination and modification of these materials, the curing strength and sealing properties of the leak plugging agent are improved.

Benefits of technology

The high-strength curing and good sealing of the leak plugging agent are achieved, reducing the possibility of secondary leakage and improving the leakage plugging efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention proposes a plugging agent for a carbon dioxide gas drive well and a preparation method thereof, and relates to the field of oil production. By weight, the following raw materials are included: 20-30 parts of oil well cement, 10-15 parts of nano calcium carbonate, 1-5 parts of modified silicon dioxide, 1-5 parts of water reducer, 5-10 parts of modified montmorillonite, and 1-5 parts of porous magnesium oxide particles. After the nano calcium carbonate, modified silicon dioxide, water reducer, modified montmorillonite and porous magnesium oxide particles are mixed evenly, the oil well cement is added and mixed evenly. The plugging agent has high strength after curing, good sealing performance with the plugging place, and is not easy to cause secondary leakage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of petroleum exploitation, and in particular to a plugging agent for a carbon dioxide gas drive well and a preparation method thereof. Background Art

[0002] CO2 gas drive oil recovery is to inject CO2 gas into the oil layer to effectively drive the formation crude oil to the production well, which can increase the oil recovery rate of the oil field. However, due to factors such as the low viscosity and density of CO2 gas, the heterogeneity of the oil reservoir, the permeability, the vertical heterogeneity of the oil reservoir, the development of fractures, the sedimentary characteristics, and the physical properties of the reservoir, CO2 is prone to crossflow during the oil drive process, reducing the crude oil recovery rate; affecting the stability of the system operation, causing accidents such as pipeline condensation and leakage of sealing packing.

[0003] The use of plugging agents to seal cracks and leaking layers in oil wells to prevent and control gas channeling can effectively reduce the accident rate. The overall strength of existing plugging agents is not high. After the plugging agents are solidified, fine cracks and micropores are easily generated at the plugging points. The plugging is incomplete and leakage still exists. Summary of the invention

[0004] The object of the present invention is to provide a plugging agent for carbon dioxide gas drive wells, which has high strength after solidification, good sealing performance with the plugging position and is not easy to cause secondary leakage.

[0005] Another object of the present invention is to provide a method for preparing a plugging agent for carbon dioxide gas drive wells, which is simple and quick.

[0006] The present invention solves the technical problem by adopting the following technical solutions.

[0007] On the one hand, an embodiment of the present invention provides a plugging agent for carbon dioxide gas drive wells, which includes the following raw materials by weight: 20-30 parts of oil well cement, 10-15 parts of nano calcium carbonate, 1-5 parts of modified silicon dioxide, 1-5 parts of water reducer, 5-10 parts of modified montmorillonite, and 1-5 parts of porous magnesium oxide particles;

[0008] The modified silicon dioxide is obtained by modifying polystyrene sulfonic acid and hydroxypropyltrimethoxysilane; and the modified montmorillonite is obtained by modifying limestone and gelatin.

[0009] In some embodiments of the present invention, the modified silica is prepared by the following method: polystyrene sulfonic acid and water are stirred and mixed evenly, and then hydroxypropyl trimethoxy silane is added dropwise, centrifuged, filtered, and dried. The mass ratio of the polystyrene sulfonic acid, the hydroxypropyl trimethoxy silane and water is (10-20): (1-5): 100.

[0010] In some embodiments of the present invention, the modified montmorillonite is prepared by the following method:

[0011] Mix limestone powder with water, shake it ultrasonically, let it stand, and take the limestone water supernatant;

[0012] The montmorillonite and the limestone water supernatant are mixed evenly, subjected to ultrasonic vibration treatment for 10-30 minutes, allowed to stand, and the supernatant is removed; filtered, dried, and crushed to obtain particles;

[0013] At 50-60° C., gelatin and water are mixed and stirred evenly, and then the granules are added and stirred evenly, and then allowed to stand for 5-10 hours, dried and crushed to obtain the modified montmorillonite.

[0014] The mass volume ratio of montmorillonite to limestone supernatant is 1g: (5-10)ml.

[0015] In some embodiments of the present invention, the particle size of nano calcium carbonate is 100-200 nm.

[0016] In some embodiments of the present invention, the water reducing agent is calcium lignin sulfonate or sodium lignin sulfonate.

[0017] In some embodiments of the present invention, the porous magnesium oxide particles are prepared by the following method:

[0018] The magnesium nitrate solution and the sodium carbonate solution are mixed evenly, added into a reaction kettle, reacted at 150°C for 5-10 hours, the supernatant is removed, and then roasted at 650-700°C for 1-2 hours, crushed to obtain granules; cyclodextrin is mixed with water, stirred evenly, and then the granules are added, stirred for 1-2 hours, allowed to stand, filtered, dried, and crushed to obtain the porous magnesium oxide particles.

[0019] In some embodiments of the present invention, the mass ratio of cyclodextrin, particulate matter and water is: (1-2): (1-2): (20-30).

[0020] On the other hand, an embodiment of the present invention provides a method for preparing a plugging agent for carbon dioxide gas drive wells, comprising the following steps: mixing the nano calcium carbonate, modified silica, water reducer, modified montmorillonite and porous magnesium oxide particles evenly, then adding oil well cement and mixing evenly.

[0021] Compared with the prior art, the embodiments of the present invention have at least the following advantages or beneficial effects:

[0022] The plugging agent provided by the present invention uses oil well cement as the main raw material, and is matched with nano calcium carbonate, modified silicon dioxide, water reducing agent, modified montmorillonite, and porous magnesium oxide particles. The plugging agent powder composed of the plugging agent is fine and fine, has good injectability, high strength after curing, good sealing performance with the plugging part, and is not easy to leak secondary. The nano calcium carbonate particles are small, and can be added to the oil well cement as a reinforcing agent, and can be embedded in the cement during curing to improve the strength of the cement; the montmorillonite has a multilayer structure and has certain water absorption. During the curing process, the montmorillonite after absorbing water can form a glue, thereby increasing the viscosity of the plugging agent, so that it is not easy to be washed away by the well fluid in the early stage of curing, and the plugging efficiency is improved. DETAILED DESCRIPTION

[0023] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0024] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other. The present invention will be described in detail below with reference to specific embodiments.

[0025] On the one hand, an embodiment of the present invention provides a plugging agent for carbon dioxide gas drive wells, which includes the following raw materials by weight: 20-30 parts of oil well cement, 10-15 parts of nano calcium carbonate, 1-5 parts of modified silica, 1-5 parts of water reducer, 5-10 parts of modified montmorillonite, and 1-5 parts of porous magnesium oxide particles.

[0026] In some embodiments of the present invention, modified silica is prepared by the following method: polystyrene sulfonic acid and water are stirred and mixed evenly, and then hydroxypropyl trimethoxy silane is added dropwise, centrifuged, filtered, and dried. The mass ratio of the polystyrene sulfonic acid, the hydroxypropyl trimethoxy silane and water is (10-20): (1-5): 100. The modified silica prepared by the above method has both hydrophilic groups and lipophilic groups on its surface, and has excellent dispersibility in water and oil; during the cement hydration process, the hydrophilic groups can improve the dispersibility of the modified silica in cement, so that the modified silica can be embedded in the cement-forming molecules, thereby increasing the strength.

[0027] In some embodiments of the present invention, the modified montmorillonite is prepared by the following method:

[0028] Mix limestone powder with water, shake it ultrasonically, let it stand, and take the limestone water supernatant;

[0029] The montmorillonite and the limestone water supernatant are mixed evenly, subjected to ultrasonic vibration treatment for 10-30 minutes, allowed to stand, and the supernatant is removed; filtered, dried, and crushed to obtain particles;

[0030] At 50-60° C., gelatin and water are mixed and stirred evenly, and then the granules are added and stirred evenly, and then allowed to stand for 5-10 hours, dried and crushed to obtain the modified montmorillonite.

[0031] The modified montmorillonite provided by the present invention is first mixed with limestone aqueous solution, and under the action of water, montmorillonite absorbs water and swells, and calcium hydroxide is embedded in the interlayer structure of montmorillonite at the same time, and then montmorillonite is wrapped with gelatin aqueous solution, and montmorillonite and calcium hydroxide can be better wrapped up. When the plugging agent is used, the plugging agent is injected into the oil well, and under the action of high temperature, the gelatin on the surface decomposes and falls off, and montmorillonite contacts with water, absorbs water and swells, and increases the viscosity of the plugging agent. After the plugging agent is solidified, if microcracks are generated, when carbon dioxide gas drive is carried out, the calcium hydroxide between the montmorillonite layers can react with carbon dioxide, water, etc. to generate calcium carbonate, block microcracks, realize plugging agent self-repair, and extend the plugging time. On the other hand, the calcium hydroxide between the montmorillonite layers can participate in the cement curing process, form an integral structure with cement, strengthen the connection strength of montmorillonite and cement, and then provide overall strength. Secondly, the modified montmorillonite wrapped in gelatin also has a slow-release effect. At room temperature, gelatin dissolves slowly and has a low solubility. That is, after the plugging agent is mixed with water but not injected into the oil well, gelatin can protect the montmorillonite and prevent it from swelling in advance. After being injected into the oil well, the gelatin dissolves faster under the action of high temperature, and the montmorillonite comes into contact with water, thereby increasing the viscosity of the plugging agent, which is conducive to adhering to the cracks and facilitating solidification and molding.

[0032] In some embodiments of the present invention, the mass volume ratio of montmorillonite to limestone supernatant is 1 g: (5-10) ml.

[0033] In some embodiments of the present invention, the particle size of nano calcium carbonate is 100-200 nm.

[0034] In some embodiments of the present invention, the water reducing agent is calcium lignin sulfonate or sodium lignin sulfonate.

[0035] In some embodiments of the present invention, the porous magnesium oxide particles are prepared by the following method:

[0036] The magnesium nitrate solution and the sodium carbonate solution are mixed evenly, added to the reactor, reacted at 150°C for 5-10 hours, the supernatant is removed, and then roasted at 650-700°C for 1-2 hours, crushed, and granules are obtained; cyclodextrin is mixed with water, stirred evenly, and then the granules are added, stirred for 1-2 hours, allowed to stand, filtered, dried, and crushed to obtain the porous magnesium oxide particles. Cyclodextrin is used to wrap the magnesium oxide particles. During the hydration process, the cyclodextrin dissolves in water and is combined with the gel of the modified montmorillonite to work together to increase the viscosity of the plugging agent.

[0037] In some embodiments of the present invention, the mass ratio of cyclodextrin, particulate matter and water is: (1-2): (1-2): (20-30).

[0038] On the other hand, an embodiment of the present invention provides a method for preparing a plugging agent for carbon dioxide gas drive wells, comprising the following steps: mixing the nano calcium carbonate, modified silica, water reducer, modified montmorillonite and porous magnesium oxide particles evenly, then adding oil well cement and mixing evenly.

[0039] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0040] Example 1

[0041] 1. Preparation of modified silica:

[0042] The polystyrene sulfonic acid and water are stirred and mixed evenly, and then hydroxypropyl trimethoxy silane is added dropwise, centrifuged, filtered, and dried. The mass ratio of polystyrene sulfonic acid, the hydroxypropyl trimethoxy silane and water is 10:5:100.

[0043] 2. Preparation of modified montmorillonite:

[0044] Mix limestone powder with water, shake it ultrasonically, let it stand, and take the limestone water supernatant;

[0045] The montmorillonite and the limestone water supernatant are mixed evenly, subjected to ultrasonic vibration treatment for 30 minutes, allowed to stand, and the supernatant is removed; filtered, dried, and crushed to obtain particles; the mass volume ratio of the montmorillonite to the limestone supernatant is 1 g:5 ml.

[0046] At 50-60° C., gelatin and water are mixed and stirred evenly, and then the granules are added and stirred evenly, and then allowed to stand for 10 hours, dried and crushed to obtain the modified montmorillonite.

[0047] Among them, the mass ratio of cyclodextrin, particulate matter and water is 1:1:20.

[0048] 3. Preparation of porous magnesium oxide particles:

[0049] The magnesium nitrate solution and the sodium carbonate solution are mixed evenly, added into a reactor, reacted at 150°C for 10 hours, the supernatant is removed, and then roasted at 700°C for 2 hours and crushed to obtain granules; cyclodextrin is mixed with water, stirred evenly, and then the granules are added, stirred for 2 hours, allowed to stand, filtered, dried, and crushed to obtain the porous magnesium oxide particles.

[0050] 4. Preparation of plugging agent:

[0051] Prepare the raw materials according to the following proportions: 30 parts of oil well cement, 15 parts of nano calcium carbonate, 5 parts of modified silica, 5 parts of water reducer (calcium lignin sulfonate), 10 parts of modified montmorillonite, and 5 parts of porous magnesium oxide particles.

[0052] Prepare the plugging agent as follows:

[0053] The nano calcium carbonate, modified silicon dioxide, water reducing agent, modified montmorillonite and porous magnesium oxide particles are mixed evenly, and then oil well cement is added and mixed evenly.

[0054] Example 2

[0055] Prepare the raw materials according to the following ratio:

[0056] 20 parts of oil well cement, 15 parts of nano calcium carbonate, 3 parts of modified silicon dioxide, 3 parts of water reducer (calcium lignin sulfonate), 8 parts of modified montmorillonite, and 3 parts of porous magnesium oxide particles.

[0057] Wherein, the modified silicon dioxide, modified montmorillonite and porous magnesium oxide particles are all prepared by the method of Example 1.

[0058] The nano calcium carbonate, modified silicon dioxide, water reducing agent, modified montmorillonite and porous magnesium oxide particles are mixed evenly, and then oil well cement is added and mixed evenly to obtain the plugging agent of this embodiment.

[0059] Example 3

[0060] Prepare the raw materials according to the following ratio:

[0061] 25 parts of oil well cement, 10 parts of nano calcium carbonate, 1 part of modified silica, 1 part of water reducer (calcium lignin sulfonate), 10 parts of modified montmorillonite, and 1 part of porous magnesium oxide particles.

[0062] Wherein, the modified silicon dioxide, modified montmorillonite and porous magnesium oxide particles are all prepared by the method of Example 1.

[0063] The nano calcium carbonate, modified silicon dioxide, water reducing agent, modified montmorillonite and porous magnesium oxide particles are mixed evenly, and then oil well cement is added and mixed evenly to obtain the plugging agent of this embodiment.

[0064] Example 4

[0065] Prepare the raw materials according to the following ratio:

[0066] 20 parts of oil well cement, 10 parts of nano calcium carbonate, 5 parts of modified silicon dioxide, 5 parts of water reducer (sodium lignin sulfonate), 5 parts of modified montmorillonite, and 5 parts of porous magnesium oxide particles.

[0067] Wherein, the modified silicon dioxide, modified montmorillonite and porous magnesium oxide particles are all prepared by the method of Example 1.

[0068] The nano calcium carbonate, modified silicon dioxide, water reducing agent, modified montmorillonite and porous magnesium oxide particles are mixed evenly, and then oil well cement is added and mixed evenly to obtain the plugging agent of this embodiment.

[0069] Example 5

[0070] Prepare the raw materials according to the following ratio:

[0071] 25 parts of oil well cement, 13 parts of nano calcium carbonate, 1 part of modified silicon dioxide, 3 parts of water reducer (sodium lignin sulfonate), 8 parts of modified montmorillonite, and 1 part of porous magnesium oxide particles.

[0072] Wherein, the modified silicon dioxide, modified montmorillonite and porous magnesium oxide particles are all prepared by the method of Example 1.

[0073] The nano calcium carbonate, modified silicon dioxide, water reducing agent, modified montmorillonite and porous magnesium oxide particles are mixed evenly, and then oil well cement is added and mixed evenly to obtain the plugging agent of this embodiment.

[0074] Example 6

[0075] Based on Example 1, the difference between this example and Example 1 is that when preparing the modified silicon dioxide, the mass ratio of polystyrene sulfonic acid, the hydroxypropyltrimethoxysilane and water is 20:5:100. The rest of the raw materials and preparation method are the same as those in Example 1.

[0076] Example 7

[0077] Based on Example 1, the difference between this example and Example 1 is that when preparing the modified silicon dioxide, the mass ratio of polystyrene sulfonic acid, the hydroxypropyltrimethoxysilane and water is 15:3:100. The rest of the raw materials and preparation method are the same as those of Example 1.

[0078] Example 8

[0079] Based on Example 1, the difference between this example and Example 1 is that when preparing the modified montmorillonite, the mass volume ratio of montmorillonite to limestone supernatant is 1 g:10 ml. The rest of the raw materials and preparation method are the same as those in Example 1.

[0080] Example 9

[0081] Based on Example 1, the difference between this example and Example 1 is that when preparing the modified montmorillonite, the mass volume ratio of montmorillonite to limestone supernatant is 1 g:8 ml. The rest of the raw materials and preparation method are the same as those in Example 1.

[0082] Example 10

[0083] Based on Example 1, the difference between this example and Example 1 is that when preparing the porous magnesium oxide particles, the mass ratio of cyclodextrin, particles and water is 1:2:30. The remaining raw materials and preparation methods are the same as those of Example 1.

[0084] Embodiment 11

[0085] Based on Example 1, the difference between this example and Example 1 is that when preparing the porous magnesium oxide particles, the mass ratio of cyclodextrin, particles and water is 2:2:30. The rest of the raw materials and preparation methods are the same as those of Example 1.

[0086] Comparative Example 1

[0087] The difference from Example 1 is that in this comparative example, nano silicon dioxide is used instead of modified silicon dioxide, and the remaining raw materials and preparation method are the same as those of Example 1.

[0088] Comparative Example 2

[0089] The difference from Example 1 is that in this comparative example, montmorillonite is used instead of modified montmorillonite, and the remaining raw materials and preparation method are the same as those of Example 1.

[0090] Comparative Example 3

[0091] The difference from Example 1 is that in this comparative example, magnesium oxide is used instead of porous magnesium oxide particles, and the remaining raw materials and preparation method are the same as those of Example 1.

[0092] Comparative Example 4

[0093] The difference from Example 1 is that in this comparative example, montmorillonite is used instead of modified montmorillonite, montmorillonite is used instead of modified montmorillonite, and magnesium oxide is used instead of porous magnesium oxide particles. The remaining raw materials and preparation methods are the same as those in Example 1.

[0094] Experimental example

[0095] 1. Compressive strength

[0096] Take 30g of the plugging agent of Examples 1-5 and Comparative Examples 1-4 respectively, add 80g of water, stir evenly, and pour into a mold with a bottom radius of 2cm and a height of 10cm. Each implementation corresponds to 3 molds, that is, 3 parallel experiments. Then, after curing each mold at 90℃ for 24h, the compressive strength of each group of hardened plugging materials is tested. The compressive strength test method and standard refer to Q / SLCG0095-2014. The results are shown in Table 1. It should be noted that the values ​​in the table are the average values ​​of the data of 3 parallel groups of the same embodiment.

[0097] Table 1 Compressive strength of each plugging agent after curing

[0098]

[0099] It can be concluded from Table 1 above that the plugging agents of Examples 1-5 provided by the present invention can reach a compressive strength of more than 40MPa after curing at 90°C for 24 hours. The raw materials of Comparative Examples 1-4 are different from those of Example 1, and accordingly, the compressive strength is also reduced. Conventional nano-silicon dioxide is used in Comparative Example 1, and its uniformity of dispersion in water is poor. During the curing process, the uneven dispersion of nano-silicon dioxide leads to uneven distribution of compressive properties, thereby affecting the overall strength. In Comparative Example 2, unmodified montmorillonite is used, and its interlayer does not contain calcium hydroxide. During the curing process, the connectivity between montmorillonite and cement is poor, and it is difficult to form a whole, resulting in a decrease in its strength. In Comparative Example 3, porous magnesium oxide particles are not used, which also has a certain impact on its compressive strength.

[0100] 2. Plugging performance test

[0101] Several artificial cores with the same cracks were selected, and the initial permeability was tested. 500 ml of the plugging agent mixture of Examples 1-5 and Comparative Example 2 (prepared at a ratio of 30 g plugging agent: 80 g water) was injected into the artificial cores through a constant pressure and constant speed pump. After the injection was completed, the cores were reacted in a constant temperature oven at 90°C for 24 hours, and then CO2 was injected for a displacement experiment. The permeability of each example after 24 hours, 48 ​​hours and 72 hours was tested and the plugging efficiency was calculated. The results are shown in Table 2.

[0102] Table 2 The plugging effect of each plugging agent

[0103]

[0104] From the data in Table 2, it can be concluded that the plugging effects of the plugging agents of Examples 1-5 are all above 90% in the initial and later stages, and the plugging effects of the plugging agents are excellent as time goes by. The plugging effect of Comparative Example 2 is poor, and the plugging rate decreases after 72 hours.

[0105] In summary, the plugging agent proposed in the embodiment of the present invention uses oil well cement as the main raw material, and is matched with nano calcium carbonate, modified silica, water reducing agent, modified montmorillonite, and porous magnesium oxide particles. The plugging agent powder composed of the plugging agent is fine and has good injectability, high strength after curing, good sealing performance with the plugging part, and is not prone to secondary leakage. The particles of nano calcium carbonate are small and can be added to oil well cement as a reinforcing agent. They can be embedded in cement during curing to improve the strength of cement; montmorillonite has a multilayer structure and has certain water absorption. During the curing process, the montmorillonite after absorbing water can form a glue, thereby increasing the viscosity of the plugging agent, making it difficult to be washed away by the well fluid in the early stage of curing, thereby improving the plugging efficiency.

[0106] The embodiments described above are part of the embodiments of the present invention, rather than all of the embodiments. The detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

Claims

1. A plugging agent for carbon dioxide gas drive wells, characterized in that: The following raw materials are included by weight: 20-30 parts of oil well cement, 10-15 parts of nano calcium carbonate, 1-5 parts of modified silicon dioxide, 1-5 parts of water reducing agent, 5-10 parts of modified montmorillonite, 1-5 parts of porous magnesium oxide particles; The modified silicon dioxide is prepared by the following method: polystyrene sulfonic acid and water are stirred and mixed evenly, and then hydroxypropyltrimethoxysilane is added dropwise, centrifuged, filtered, and dried; The modified montmorillonite is obtained by embedding calcium hydroxide into the interlayer structure of montmorillonite and then wrapping the montmorillonite with a gelatin aqueous solution. The modified montmorillonite is prepared by the following method: mixing limestone powder with water, ultrasonically vibrating, standing, and taking the limestone water supernatant; The montmorillonite and the limestone water supernatant are mixed evenly, subjected to ultrasonic vibration treatment for 10-30 minutes, allowed to stand, and the supernatant is removed; filtered, dried, and crushed to obtain particles; At 50-60° C., gelatin and water are mixed and stirred evenly, and then the granules are added, stirred evenly, left to stand for 5-10 hours, dried, and crushed to obtain the modified montmorillonite; The porous magnesium oxide particles are prepared by the following method: The magnesium nitrate solution and the sodium carbonate solution are mixed evenly, added into a reaction kettle, reacted at 150°C for 5-10 hours, the supernatant is removed, and then roasted at 650-700°C for 1-2 hours, crushed to obtain granules; cyclodextrin is mixed with water, stirred evenly, and then the granules are added, stirred for 1-2 hours, allowed to stand, filtered, dried, and crushed to obtain the porous magnesium oxide particles.

2. The plugging agent for carbon dioxide gas drive well according to claim 1, characterized in that: The mass ratio of the polystyrene sulfonic acid, the hydroxypropyltrimethoxysilane and water is (10-20):(1-5):

100.

3. The plugging agent for carbon dioxide gas drive well according to claim 1, characterized in that: The mass volume ratio of montmorillonite to limestone supernatant is 1g: (5-10)ml.

4. The plugging agent for carbon dioxide gas drive well according to claim 1, characterized in that: The particle size of the nano calcium carbonate is 100-200nm.

5. The plugging agent for carbon dioxide gas drive well according to claim 1, characterized in that: The water reducing agent is calcium lignin sulfonate or sodium lignin sulfonate.

6. The plugging agent for carbon dioxide gas drive well according to claim 1, characterized in that: The mass ratio of cyclodextrin, particulate matter and water is: (1-2): (1-2): (20-30).

7. A method for preparing a plugging agent for carbon dioxide gas drive wells according to any one of claims 1 to 6, characterized in that: The following steps are involved: The nano calcium carbonate, modified silicon dioxide, water reducing agent, modified montmorillonite and porous magnesium oxide particles are mixed evenly, and then oil well cement is added and mixed evenly.

Citation Information

Patent Citations

  • High-strength consolidation lost circulation additive

    CN103773340A

  • Water control fracturing stimulation method for oil and gas well

    CN111022020A

  • Silicon dioxide dispersion as well as preparation method and application thereof

    CN117165102A